Methodological approaches to assessing the level of digitalization of the construction site - Dubinin, D.; Filippov, O. (Ways to Improve Construction Efficiency, 2023)
The article explores the important area of assessing the degree of digitization of construction sites. As the construction industry undergoes digital transformation, understanding and quantifying the degree of digitization becomes key for stakeholders, including project managers, contractors and technology providers. VIM technologies are an actual area of research. due to the growing importance of digitization in construction, the recognition of its potential to improve efficiency, collaboration and overall project results, there is a growing need for a systematic and comprehensive methodology to assess the level of digitization, taking into account the multifaceted nature of construction projects. The methodology proposed in the paper covers various aspects of digitization, from the implementation of Building Information Modeling (BIM) and the use of digital tools to the integration of Internet of Things (IoT) devices on site, a structured methodology and framework that includes Key Performance Indicators (KPIs) or metrics is proposed to measure the digital maturity of construction activities. The study draws on existing literature and case studies to support its methodological approaches, providing a synthesized view of best practices and successful implementations in the construction industry, including references to specific projects that have effectively used digitization to achieve better project outcomes, cost savings or accelerated timelines. In addition, challenges and barriers related to the digitization of construction sites, issues related to technology adoption, workforce training, data security and digital tool interoperability are explored. Addressing these issues within the framework of the proposed methodological approaches will increase the practical applicability of recommendations, informed decision-making, optimization of resources and the overall progress of the construction industry towards more technological and sustainable practices. The study contributes to the field of construction management and technology by offering a structured and methodical approach to assessing the level of digitization on construction sites. By combining theoretical foundations with practical research knowledge, it can serve as a reference for professionals and researchers seeking to achieve digital transformation in the construction industry.